Fundamentals of Entrepreneurship ENT 300 : Vicone / Brandon Russell Belayong Lawrance ... [et al.] - Lawrance, Brandon Russell Belayong; Lidy, Henry Ngumbang; Nelkom, Nicholson Josin; Freddy, Andrias Lenjau (2019)
Everyone in the organization will use the information contained in the business plan whether to set performance target, guide decision with regard to ongoing operation or assess personnel performance in term of their ability to meet objectives in business plan. A business’s performance and progress can be measure within planned goals involving sales, expenditures, time frame and strategic direction. Business plan also help an entrepreneur or a business manager identify and focus on potential problem areas, both inside and outside the organization. This business plan is the guideline for the organization in setting, planning, managing, handling and controlling our business for day to day management, budget, financial forecast, strategies, target market and even long term goals. It is also as a master plan of an organization that necessary to calculate the effectiveness on running such business. As successful business leader knows that a well written business plan can provide day to day operational assistant. Organization that concentrated on their business have a higher chance of success; when used as road map, it can help business leaders stay focused on business growth, mission and organization’s goal.